Comparison of the Variation Characteristics and Influencing Factors of Evapotranspiration in Two Alpine Grasslands on the Qinghai-Xizang Plateau - Chun PU; Bin YANG; Yanggang ZHAO; Lun LUO; Xunxun ZHANG; Yanghai DUAN (Science Press, PR China, 2024)
In the context of global warming， the Qinghai-Xizang Plateau is altering atmospheric circulation through sensible heat absorption and latent heat release.This not only impacts the water and energy balance of the plateau's ecosystem but also plays a crucial role in regulating Asian and global climates.In order to explore the change characteristics and influencing factors of evapotranspiration in different regions of alpine grassland ecosystem on the Qinghai-Xizang Plateau， and deepen understanding of plateau climate change and hydrological-ecological processes， based on the observed eddy and meteorological data in 2022， the variation characteristics and environmental influencing factors of actual evapotranspiration of alpine grassland ecosystems at the same altitude in Sijinlacuo （seasonal permafrost） and Tuotuo River （permafrost） on the Qinghai-Xizang Plateau were compared and analyzed.The results show that： （1） Significant differences existed between environmental factors at these two sites， particularly in wind speed， air temperature， and precipitation.The wind speed at Tuotuo River station greatly exceeded that at Shijinlasuo station； annual average air temperature and precipitation were lower at Tuotuo River station.（2） The average hourly evapotranspiration of Sijinlacuo Station at night was higher than those recorded at Tuotuo River Station， however， this trend reverses during daytime hours.The variation characteristics of daily evapotranspiration at the two stations had a similar trend.The date of sharp increase and maximum of evapotranspiration at Sijinlacuo Station were earlier than those at Tuotuo River Station.The monthly evapotranspiration of the two stations were unimodal， with the maximum value appeared in July in summer and the smaller value appeared in December， January and February in winter.（3） Wind speed and ground radiation showed differing correlations with evaporation across both stations.Wind speed had a stronger correlation with evaporation at Tuotuo River Station due to higher wind speeds ...